IMPLEMENTASI DIGITALISASI REKAM MEDIS DALAM KEGIATAN REKAM MEDIS ELEKTRONIK DI RSIA BUDHI MULIA PEKANBARU - Henny Maria Ulfa; Haryani Octaria; Tona Doli Silitonga (Journal of Hospital Administration and Management (JHAM), 2026)
The implementation of Electronic Medical Records (EMR) is an essential component of digital transformation in healthcare services and has become mandatory for all healthcare facilities in Indonesia. One of the key elements supporting EMR implementation is medical record digitization, which aims to improve the efficiency of patient data management and facilitate timely access to health information. This study aimed to analyze the implementation of medical record digitization in Electronic Medical Record activities at RSIA Budhi Mulia Pekanbaru. This study employed a descriptive qualitative approach. Four informants participated in the study, consisting of the head of the medical record unit, registration officers, and medical record processing staff. Data were collected through observation, in-depth interviews, and documentation, and analyzed using qualitative methods. The findings revealed that medical record personnel involved in the digitization process possessed appropriate educational qualifications and had received training related to EMR implementation. Standard Operating Procedures (SOPs) for EMR implementation were available and consistently applied. Supporting facilities and infrastructure, including computer equipment and internet networks, were considered adequate. However, a weakness was identified in the system security aspect, namely the absence of an automatic account-locking feature, which may increase the risk of unauthorized access to medical record data. The study concludes that the implementation of medical record digitization at RSIA Budhi Mulia Pekanbaru has generally been well implemented in terms of human resources, SOPs, and supporting infrastructure. Strengthening system security through the development of account protection features is recommended to enhance the confidentiality and integrity of electronic medical record data.